Modern Pesantren (Islamic Boarding School): Competitive Advantages in Darul Yatama Wal-Masakin (Dayama) Islamic Boarding School in Jerowaru East Lombok - S. Ali Jadid Al Idrus (LP2M STIT Palapa Nusantara, 2020)
Nowadays, Islamic boarding schools have experienced a very significant change considering the current of globalization which is increasingly expanding to all sides of human life. To be able to compete in this era, Islamic boarding schools – in one hand - must work together with other institutions and make changes by applying management as a foundation in developing boarding schools on the other, in order to be able to compete and become a modern boarding school in all fields such as entrepreneurship boarding school. This study aims to determine entrepreneurship planning, management strategies used and marketing management of Darul Yatama Wal-Masakin Islamic boarding school. This study used qualitative research with a descriptive approach. Data collection techniques carried out by unstructured interviews, non-participant observation, and documentation. The data were analyzed with an interactive model consisting of data collection, data reduction, data display, and conclusion. Checking the data validation was done by increasing the perseverance of observation and triangulation. Based on the results of this study, it was found that; a) Entrepreneurship planning started from the results of the fundamental thinking of its founder, namely TGH. Muhammad Mutawalli Yahya Al-Kalimi with the concept of independence. The concept of independence that he initiated was to prepare facilities that can be used as a source of funds to finance the management of the Islamic boarding schools; b) Management strategies in developing entrepreneurship can be seen from the business units developed such as: gas stations, animal husbandry, agriculture, fisheries and cooperatives. c) Marketing management used was involving and making all society as partners in every business that was developed.